Padre Cícero do Juazeiro do Norte: a construção do mito e seu alcance social e religioso - Tolovi, Carlos Alberto (2016)
Taking the figure of Padre Cícero as reference it is possible to realize a sanctification that coincides with the construction of a myth. However, this mythologized saint has something of specific: he was constructed by popular religiousness and yet today belongs to that. After all, the Juazeiro do Norte's patriarch affectionately called meu padim , is a saint that lives at sun by the fact that he was removed from the priestly orders. Eclesial decision that remains until nowadays. Padre Cicero hasn't yet rehabilitated by the hierarchy of the Catholic Church. In spite of he is proclaimed saint by his pilgrims , however, but he can't g in the Catholic Church and occupy a place beside the other saints - Europeans in its majority. This comes from a colonialist ideology that, by means of the control of sacred establish a balance of power characterized as clerical, centralizing and hierarchical. A historic reality that just can be realized through a broader scenario, where were inserted persons like Padre Ibiapina, Conselheiro and Zé Lourenço. In this scenario we can observe big and outstanding conflicts between the hierarchy of the Catholic Church, the popular religiosity and the Brazilian State. It is inside this contexto that we look for to realize the structure of the myth around the figure of Padre Cicero. An enigmatic and contradictory person. However, from the point of view of the popular religiosity he is inserted inside a coherent and full of meaning universe, in the fight of survival, open loopholes in the constructed power structures. It is in this perspective that can realize the mythicizing process involving the person of Pe. Cicero, with direct impacts on the political, social and economic reality of Juazeiro do Norte, in the region of Cariri, in Ceará state, with immediate reflexes in fight scenarios by the power in a national level. At last, from Pe. Cicero and Juazeiro do Norte we can realize that the myth posseses a closed link nfluencing directly the social relations